Swot Analysis of the Self Help Groups (Indian Journal of Extension Education, 2014)
Self help groups (SHGs) have been instrumental in women empowerment by enabling them to work together. The present investigation was carried out in Punjab to determine the participation of members of self help groups in training and to evaluate the self help groups in the light of SWOT (strengthens, weaknesses, opportunities, and threats ) analysis of the members as perceived by the managers of promoting agencies. Majority of the members of self help groups participated in various training programmes on product preparation and capacity building of the SHGs. Majority of the respondents (83.33%) reported that linkages with line departments and regularity in savings (75%) were the major strengthening points while half of the respondents observed group crisis and non-cooperation of the family members as the major weaknesses that hindered the faithful performance of the group. The findings further revealed that increased income (83.33%), employment generation (75%) and more savings (66.66%) were the major opportunities while problem of good quality raw material (83.33%) and lack of legal status (66.66%) were the threats as perceived by the majority of managers of promoting agencies. Therefore, it is suggested that managers should take care of SWOT analysis of the groups for its future promotion.